Identification of transmission line parameters from temporal measurements of currents and voltages in their terminals: Influence oh the length line - Asti, G. A. [UNESP]; Da Silva, R. C. [UNESP]; Kurokawa, S. [UNESP]; Da Costa, E. C M (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The objective of this paper is to show a methodology to estimate transmission line parameters. The method is applied in a single-phase transmission line using the method of least squares. In this method the longitudinal and transversal parameters of the line are obtained as a function of a set of measurements of currents and voltages (as well as their derivatives with respect to time) at the terminals of the line during the occurrence of a short-circuit phase-ground near the load. The method is based on the assumption that a transmission line can be represented by a single circuit π. The results show that the precision of the method depends on the length of the line, where it has a better performance for short lines and medium length. © 2012 IEEE.
Keywords: Least-squares method; Parameters estimation; Transmission line modeling; Transmission lines; Currents and voltages; Least squares methods; Method of least squares; Temporal measurements; Transmission line parameters; Electric lines; Least squares approximations; Transmission line theory